Motivational factors for enrolling in mass communication in different tertiary schools in Iloilo City. - Garzon, Rhoda Acana
This study seeks to find out the reasons why students enroll in Mass Communication and to determine the number of enrollees from 1999-2004. This study is significant to the universities and state colleges, school administrators, and division chairs or heads. The study is focused on the reasons that lead students to enroll in the program. The study is limited to the following universities: Central Philippine University, St. Paul's University of Iloilo, University of Iloilo and West Visayas State University. The results revealed that the highest number of enrollees in Mass Communication program came from West Visayas State University. The respondents identified that personal reasons were their primary reasons for enrolling in Mass Communication. Most of the respondents identified that they want to voice out their opinions against the government, the job opportunity that awaits them, and it is their personal choice and interest, and they want to impart moral values taught by the church. And lastly, they want to improve their communication/speaking abilities. The results also suggest that Mass Communication program has experienced a steady decrease in enrollment from 1999-2004. The researchers recommend that schools conduct massive orientation of Mass Communication programs to graduating High School students; purchase high-tech laboratory equipment; improve existing curriculum ; and create more activities related to the course.